(UPCON) Fabrication of electro-spin coated Zn 0.97 Fe 0.03 O nano-rough thin film and application in LPG sensing - Nath Anchal B.B.; Singh P.; Pyare R. (My University, 2025)
In this paper presented to fabrication of Zn 0.97 Fe 0.03 O nano rough thin film by high rpm electro-spin technique and detection of LPG (Liquefied Petroleum Gas). The film grown technique is spin coating and doping part of 3 % iron in zinc oxide by chemical route. The Characterization of film by XRD, SEM, EDX and AFM. Observation of sensing for LPG as concentrations of 100 ppm, 300 ppm and 500 ppm at 50 °C in assembled gas sensing set up. The living maximum temperature around up to 50 °C in summer. So choosen LPG sensing at this temperature. The concept of iron doping in host zinc oxide for improved gas sensing properties. So, applied minimum 3 % iron doped zinc oxide thin film using in the sensing of LPG. The spin coating technique is inexpensive and easily operated. © 2018 IEEE.